Advances in Quercus ilex L. breeding: the CRISPR/Cas9 technology via ribonucleoproteins - Pavese, Vera; Moglia, Andrea; Milani, Anna Maria; Marino, Lorenzo Antonio; Martinez, Maria Teresa; Torello Marinoni, Daniela; Botta, Roberto; Corredoira, Elena (Frontiers in Plant Science, 2024)
The CRISPR/Cas9 ribonucleoprotein (RNP)-mediated technology represents a fascinating tool for modifying gene expression or mutagenesis as this system allows for obtaining transgene-free plants, avoiding exogenous DNA integration. Holm oak (Quercus ilex) has an important social, economic, and ecological role in the Mediterranean climate zones of Western Europe and North Africa and is severely affected by oak decline syndrome. Here we report the first example of the application of the CRISPR/Cas9-RNP technology in holm oak. Firstly, we evaluated the protoplast isolationextraction from both in vitro leaves and proembryogenic masses. Proembryogenic masses represented the best material to get high protoplast yield (11 x 10 6 protoplasts/ml) and viability. Secondly, the protoplast transfection ability was evaluated through a vector expressing green fluorescence protein as marker gene of transfection, reaching a transfection percentage of 62% after 24 hours. CRISPR/Cas9 RNPs were successfully deliveredtargeted into protoplasts resulting in 5.6% ± 0.5% ~ 5.5% of editing efficiency at phytoene desaturase (pds) target genomic region. Protoplasts were then cultured in semisolid media and, after 45 days in culture, developed embryogenic calli were observed in a Murashige and Skoog media with half concentration of NH4NO3 and KNO3 supplemented with 0.1 mg/L benzylaminopurine and 0.1 mg/L 2,4-dichlorophenoxyacetic acid. Formattato: Italiano (Italia) Formattato: Italiano (Italia) Formattato: Italiano (Italia) Formattato: Italiano (Italia) Formattato: Italiano (Italia)